Endocytoscopic Observation of Non-Ampullary Mucosal Duodenal Cancer - Youichi Kumagai; Morihiro Higashi; Shunsuke Muramatsu; Erito Mochiki; Hideyuki Ishida (Case Reports in Gastroenterology, 2020)
Our previous study of duodenal adenoma using an endocytoscopy system (ECS) demonstrated that disappearance of goblet cells and spindle-shaped nuclei with loss of polarity were characteristic features. In addition, round duct openings and finger-like projections were observed in tubular adenoma and villous adenoma, respectively. Here, we retrospectively investigated six cases of histologically proven sporadic non-ampullary mucosal duodenal cancer (NAMDC) using ECS. Immunohistochemistry for CD10, MUC2, MUC5AC, and MUC6 was employed to determine the mucin phenotype in addition to conventional HE histology. Immunohistochemistry revealed one case involving the duodenal bulb that was considered to be the mixed type. The other five cases, located in the second or third portion, were considered to be the intestinal type. Vital staining of the mixed-type case was considered insufficient for ECS observation because of surface mucus. However, all five cases of intestinal-type duodenal cancer demonstrated a villous structure, disappearance of goblet cells and enlarged nuclei with loss of polarity. Tubular structures were admixed in four of those cases. Four cases demonstrated oval-shaped nuclei, and one case had spindle-shaped nuclei. Cases showing spindle-shaped nuclei in most of the lesion were diagnosed histologically as cancer in adenoma where the adenomatous component of the tumor was dominant. Oval-shaped nuclei and nuclear enlargement are the characteristic features of NAMDC revealed by ECS and are included among the histological criteria used for diagnosis. ECS offers the potential to perform real-time histological diagnosis of NAMDC in vivo.